2018
DOI: 10.1007/s00414-018-1934-1
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of the Stoyanova et al. method (2017) for age-at-death estimation quantifying the 3D pubic symphyseal surface of adult males of European populations

Abstract: The age-at-death estimation thresholds have recently been shifted towards a more objective assessment of the aging process. Such a non-subjective approach offers quantitative methods of age estimation; for instance, the method relating to the surfaces of pubic symphyses of males published by Stoyanova et al. (J Forensic Sci 62:1434-1444, 2017). A validation study was conducted to test the method performance in European samples. The sample consisted of 96 meshes of pubic symphyses of male individuals (known sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…It should also be noted that the models of Stoyanova are restricted to male individuals only. 2018) also included male individuals only 27,57 , while Joubert et al 55 , Johnson and Bethard 54 and the present study incorporated both sexes. As the results of all the validation studies are similar, the inclusion of female individuals did not appear to affect the performance of the method.…”
Section: Validation Of Existing Algorithms (Proposed By Stoyanova Et ...mentioning
confidence: 83%
See 3 more Smart Citations
“…It should also be noted that the models of Stoyanova are restricted to male individuals only. 2018) also included male individuals only 27,57 , while Joubert et al 55 , Johnson and Bethard 54 and the present study incorporated both sexes. As the results of all the validation studies are similar, the inclusion of female individuals did not appear to affect the performance of the method.…”
Section: Validation Of Existing Algorithms (Proposed By Stoyanova Et ...mentioning
confidence: 83%
“…The most prominent computational approach for estimating adult age based on the analysis of surface changes in 3D models is the approach of Stoyanova et al (2017) 25 . We applied their ve models on our dataset and found signi cant discrepancies between the MAE (and RMSE and MBE as well) presented by Another reason for such poor results when the models of Stoyanova were applied to our or other validation datasets could partially be seen in the population speci city 27,55,56 and different aging rates between populations, since their models were proposed solely on American samples. Several studies reported population speci city when evaluating the performance of the traditional Suchey-Brooks method (e.g.…”
Section: Validation Of Existing Algorithms (Proposed By Stoyanova Et ...mentioning
confidence: 93%
See 2 more Smart Citations
“…The forAge software is one of the few age estimation approaches using mathematical quantification of bone surface that has been published so far. Repeatability of the method was tested with excellent results [60] and its use is suitable for individuals under 40 years of age [61].…”
Section: Scanning -Problem Of Compatibilitymentioning
confidence: 99%